Treatment of Pediatric Diabetic Ketoacidosis in Canada: A Review of Treatment Protocols from Canadian Pediatric Emergency Departments. Issue 6 (16th July 2015) - Skitch, Steven A; Valani, Rahim
ABSTRACT: Objective: Diabetes is the most common pediatric endocrine disorder, and diabetic ketoacidosis (DKA) is the leading cause of diabetes-related morbidity and mortality. This article reviews pediatric DKA treatment protocols from across Canada and identifies similarities and differences. Methods: Pediatric tertiary centres in Canada were asked for a copy of their DKA treatment protocol. For each protocol, we collected information on the amount of initial fluid bolus, maintenance fluid rate, insulin infusion rate, potassium replacement, monitoring and adjustment for serum glucose, administration of bicarbonate, and treatment for cerebral edema. Results: Responses were obtained from 13 sites. Treatment guidelines were consistent in their recommendations on timing and dosage of intravenous insulin, potassium replacement, monitoring and adjusting for serum glucose, and management of cerebral edema. Variability in treatment protocols was found chiefly in volume of initial fluid bolus (range: 5–20 mL/kg) and length of time boluses should be administered (20–120 min), maintenance fluid rates (based on weight or a 48-hr deficit), and the role of bicarbonate administration. Conclusions: This is the first review of treatment protocols for pediatric DKA in Canada. It identified many common approaches but noted specific differences in fluid boluses, maintenance fluid rates, and bicarbonate administration. The extent of variation indicates the need for further study, as well as national guidelines that are evidence-based and consistent with best practices. RÉSUMÉ: Objectifs: Le diabète est l'affection endocrinienne la plus fréquente chez les enfants, et l'acidocétose diabétique (ACD) est la principale cause de morbidité et de mortalité liées au diabète. Les auteurs passent en revue, dans l'article, les protocoles de traitement de l'ACD chez les enfants, appliqués partout au Canada, puis ils relèvent les ressemblances et les différences qui existent entre eux. Méthode: Les auteurs ont demandé aux centres de soins tertiaires en pédiatrie, au Canada, de leur faire parvenir une copie de leur protocole de traitement de l'ACD. Il y a eu, pour chacun d'eux, une collecte de données sur le volume initial de liquides administrés en bolus, la vitesse d'entretien de l'administration des liquides, la vitesse de perfusion de l'insuline, la recharge potassique, la surveillance de la glycémie et l'adaptation posologique, l'administration de bicarbonate ainsi que le traitement de l'œdème cérébral. Résultats: Treize centres ont accédé à la demande. Les recommandations sur le moment de l'administration de l'insuline intraveineuse et les doses prescrites, la recharge potassique, la surveillance de la glycémie et l'adaptation posologique ainsi que le traitement de l'œdème cérébral respectaient les lignes directrices relatives au traitement. Toutefois, des différences ont été relevées dans les protocoles de traitement surtout en ce qui concerne le volume initial de liquides administrés en bolus (plage: 5–20 ml/kg) et la durée d'administration des bolus (20–120 min), la vitesse d'entretien de l'administration des liquides (en fonction du poids ou de la correction de la déperdition sur 48 h) et le rôle de l'administration de bicarbonate. Conclusions: Il s'agit du premier examen méthodique des protocoles de traitement de l'ACD chez les enfants au Canada. De nombreux points communs ont été relevés, mais il existe certaines différences en ce qui concerne l'administration de liquides en bolus, la vitesse d'entretien de l'administration des liquides et l'administration de bicarbonate. L'importance des différences fait ressortir la nécessité de mener d'autres études et d'élaborer des lignes directrices nationales, fondées sur des données probantes et conformes aux pratiques exemplaires.